(untitled) (International relations and international law Journal, 2016)
In the second half of the XX century in different regions of the world have been tested numerous ways alliances, agreements, associations of different nations. Formed and entrenched a culture of integration, international experience economic and political cooperation. If at first the main criterion for the association is purely ideological affinity, already in the 80s in the first place instead of ideology began to leave the territorial proximity and historical and cultural and religious values. This fully applies to Central Asia, where the initial stage of the development of new independent states occurred updated intraregional conflicts on religious and cultural grounds or as a result of historical territorial claims, the struggle for power and positions of power in the region. After gaining independence, the Central Asian states were in weave political and economic interests of many countries, attracted by the rich resources of the region